Dimerization effect of sucrose octasulfate on rat FGF1 - Kulahin, N. (International Union of Crystallography, 2008)
Fibroblast growth factors (FGFs) constitute a family of at least 23 structurally related heparin-binding proteins that are involved in regulation of cell growth, survival, differentiation and migration. Sucrose octasulfate (SOS), a chemical analogue of heparin, has been demonstrated to activate FGF signalling pathways. The structure of rat FGF1 crystallized in the presence of SOS has been determined at 2.2 Å resolution. SOS-mediated dimerization of FGF1 was observed, which was further supported by gel-filtration experiments. The major contributors to the sulfate-binding sites in rat FGF1 are Lys113, Lys118, Arg122 and Lys128. An arginine at position 116 is a consensus residue in mammalian FGF molecules; however, it is a serine in rat FGF1. This difference may be important for SOS-mediated FGF1 dimerization in rat.